2020
DOI: 10.3390/brainsci10100675
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances on the Role of GSK3β in the Pathogenesis of Amyotrophic Lateral Sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is a common neurodegenerative disease characterized by progressive motor neuron degeneration. Although several studies on genes involved in ALS have substantially expanded and improved our understanding of ALS pathogenesis, the exact molecular mechanisms underlying this disease remain poorly understood. Glycogen synthase kinase 3 (GSK3) is a multifunctional serine/threonine-protein kinase that plays a critical role in the regulation of various cellular signaling pathways. Dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 120 publications
(165 reference statements)
0
16
0
Order By: Relevance
“…We focus on the modulation of GSK-3β, as it is recognized as one of the main kinases involved in aberrant phosphorylation of TDP-43 [5]. Moreover, alterations in GSK-3β expression and activity have been described in postmortem spinal cords and frontal and temporal cortex of ALS patients [7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…We focus on the modulation of GSK-3β, as it is recognized as one of the main kinases involved in aberrant phosphorylation of TDP-43 [5]. Moreover, alterations in GSK-3β expression and activity have been described in postmortem spinal cords and frontal and temporal cortex of ALS patients [7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal regulation of GSK-3β has been linked to both the onset and progression of different chronic conditions such as diabetes, cancer, neurodegenerative (e.g., AD, PD, ALS), and behavioral diseases (e.g., bipolar disorder (BD), major depression (MD), schizophrenia). In CNS-related disorders, aberrant GSK-3β activity is associated with the dysregulation of different proteins, namely microtubule-associated protein τ, presenilins, amyloid precursor protein (APP), collapsin response mediator proteins, components of the Wnt signaling pathway, β-catenin, and heat shock proteins [37]. Moreover, several lines of evidence have reported GSK-3β as a mediator of neuroinflammatory processes.…”
Section: Gsk-3βmentioning
confidence: 99%
“…This choice stemmed from the notion that GSK3β activation or inhibition reduces or increases VAPB-PTPIP51 interaction, respectively [ 59 ], although the molecular mechanism of such regulation is still unclear. Importantly, the perturbation of GSK3β activity was also implicated in the pathogenesis of ALS and many other neurodegenerative disorders [ 94 , 95 , 96 ]. For the first time to our knowledge, here, we demonstrated that TDP-43 down-regulation induces both an increased expression and a higher activation (i.e., reduced phosphorylation in Ser9) of GSK3β, allowing us to speculate that this pathway may significantly contribute to the reported reduction in ER–mitochondria tethering after TDP-43 silencing.…”
Section: Discussionmentioning
confidence: 99%